Limb bone histology records birth in mammals. - Carmen Nacarino-Meneses; Meike Köhler (PLoS ONE)
The annual cyclicality of cortical bone growth marks (BGMs) allows reconstruction of some important life history traits, such as longevity, growth rate or age at maturity. Little attention has been paid, however, to non-cyclical BGMs, though some record key life history events such as hatching (egg-laying vertebrates), metamorphosis (amphibians), or weaning (suggested for Microcebus and the hedgehog). Here, we investigate the relationship between non-cyclical BGMs and a stressful biological event in mammals: the moment of birth. In the present study, we histologically examine ontogenetic series of femora, tibiae and metapodia in several extant representatives of the genus Equus (E. hemionus, E. quagga and E. grevyi). Our analysis reveals the presence of a non-cyclical growth mark that is deposited around the moment of birth, analogous to the neonatal line described for teeth. We therefore refer to it as neonatal line. The presence of this feature within the bone cross-section agrees with a period of growth arrest in newborn foals regulated by the endocrine system. The neonatal line is accompanied by modifications in bone tissue type and vascularization, and has been identified in all bones studied and at different ontogenetic ages. Our discovery of a non-cyclical BGM related to the moment of birth in mammals is an important step towards the histological reconstruction of life histories in extant and fossil equids.